Effects of Climate Warming on the Performance of Gynaephora alpherakii (Lepidoptera: Lymantriidae) Larvae in a Tibetan Alpine Meadow - Rui Cao; Han Chen; Kezhi Zheng; Dajie Nong; Menglei Jiang; Ziyu Zhang; Xinwei Wu; Peng Xie (Ecology and Evolution)
ABSTRACT The performance of invertebrate herbivores in grasslands can be influenced by climate warming, but there is a lack of experimental evidence, particularly in high elevation areas. We conducted two complementary experiments to investigate the effect of experimental warming on the performance of the grassland caterpillar Gynaephora alpherakii, a notorious pest species in the alpine Tibetan meadow. The first field experiment examined the effect of warming (nonwarmed vs. warmed) on the feeding behavior, growth, and development rate of the caterpillars. The second chamber experiment explored the relationship between temperature and caterpillar appetite, excrement mass, respiration rate, or change of caterpillar weight. Results show that warming significantly decreased fresh body mass of caterpillars by 27.5%, cocoon volume by 61.1%, and egg production per female moth by 26.9% at the end of the field experiment. Warming did not affect cocooning time but significantly increased feeding time of caterpillars during the field experimental period. The independent chamber experiment revealed a significant and positive correlation between caterpillar appetite, excrement mass, respiration rate, and temperature. However, except the first examination, there was a significant negative correlation between changes in caterpillar weight and temperature. Stepwise regression analysis indicated that excrement mass had the greatest influence on caterpillar weight. The weight loss of caterpillars to warming might thus be attributed to elevated metabolic rates at higher temperatures, and the behavioral adaptations failed to compensate for the physiological‐induced weight loss. These findings suggest that climate warming can modify the performance and thus the fitness of invertebrate herbivores in high elevation areas.